Scientific and Theoretical Approach to the Management of Organic Products Promotion (Economics and region, 2021)
The article analyzes the main approaches to the management of organic products promotion, namely functional and process approaches. Based on the analysis of approaches, we linked each approach to the corresponding element of the system of the management of organic products promotion. It has been substantiated that the management based on functional and procedural approach has corresponding advantages and more effective and modern. Functional and procedural approach will ensure continuous interaction of such management functions as forecasting, planning, organization, motivation and stimulation, monitoring and control, in the process of organic products promotion, as well as sales, taking into account the life cycle of a product and customer attitude. Management of organic products promotion will be different from what exactly the products of primary production, secondary processing or finished packaged organic products is important to consider delivery times and conditions of transportation, for example, when going outside market so we would also like to consider a logistical approach to management. After all, logistics is a unifying chain between a manufacturer and a consumer, building a special structure at an enterprise in logistics systems and logistics supply chains. It is concluded that the orientation of management of organic products promotion on functional and procedural approach is a priority in today’s dynamic market environment.
Keywords: functional approach; procedural approach; organizational approach; marketing approach; management; promotion; organic products